Studi Kritik terhadap Penelitian Tasawuf, Spiritualitas, dan Kalam - Ritonga, Raja; Ritonga, Ahmad Roisuddin; Julhadi, Julhadi; Hakim, Rosniati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
The study on Sufism, spirituality, and kalam has become an intriguing subject within the scholarly realm. Adherents of Sufism focus on seeking the divine presence and direct experience with God. Spirituality refers to the non-material dimension of human existence, while kalam, as a branch of Islamic philosophy and theology, elaborates on the principles of faith and religious doctrines. This study aims to analyze scientific research related to Sufism, spirituality, and kalam. The method used is library research employing a descriptive-analytical approach. Data is collected through literature reviews, including scientific articles, books, and relevant publications related to the study's theme. The findings reveal the dynamics and tensions among these three fields, particularly in terms of methodology and objectives. Sufism and spirituality are often considered more subjective and mystical, while kalam tends to be rational and systematic. However, they complement each other in providing a comprehensive framework for understanding faith and religious practice in Islam. Furthermore, this study highlights the importance of balancing mystical experiences and rationality in developing a holistic spiritual understanding.